تصنيف العواطف في كلمات أغاني نانسي عجرم - aminatul aminatul (EL- Hayah, 2024)
Emotions are feelings that have a significant impact on behavior, so emotions are an important aspect of human life. Humans have many ways to express the emotions they feel. For example, literary works are poetry, novels, films, dramas, memoirs, biographies and songs. However, it is not rare, when someone uses a song in a foreign language to describe his feelings, the lyrics of the song do not coincide with what he wants to convey because someone does not know the translation of the lyrics of the song. Especially the meaning of the song. Research conducted by M. Rizqat Khairani and Dr. Ain Suryanengsih in analyzing the classification of love emotions for the character Laila in the novel Rebellious Spirits by Khalil Gibran explains the classification of emotions of the main character in the novel, but only the emotion of love is examined and it differs from this research which uses song objects and analyzes all classifications of emotions. This research aims to know the emotions contained in song lyrics, especially Nancy Ajram's songs, based on David Creech's theory of classification of emotions. The theory used in this research is David Creech's emotion classification theory. In his book Elements of Psychology, David Creech proposes 4 classifications of emotions, namely basic emotions (e.g. pleasure, anger, fear, sadness), emotions related to sensory stimulation (e.g. pain, disgust, enjoyment), and emotions related to self-evaluation (e.g. success and failure, pride and shame, feeling guilt and remorse), and emotions related to other people (for example: love and hate). Emotions are analyzed in this research by grouping words according to the emotional classification in each song. The research method used in this research is a qualitative descriptive research method through which the results of the analysis are described and qualified based on the theory used, which is David Creech’s theory of categorization of emotions. The results of this research are that, among the four classifications of emotions proposed by David Creech, not all classifications of emotions are found in the lyrics of Nancy Ajram's songs. In most songs, there is only one classification of emotions with one or two examples of emotions. Indeed, there is a classification of emotions that is not present in Nancy Ajram's song lyrics at all, which are emotions related to sensory stimulation (such as pain, disgust, and pleasure).